Pengaruh Kemampuan Berpikir Kritis Dan Model Pembelajaran Project Based Learning Terhadap Peningkatan Hasil Belajar Instalasi Penerangan Listrik Siswa Kelas XI TITL SMK Negeri 7 Surabaya - Ria Kharisma; Meini Sondang Sumbawati (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
Electrical Power Installation Engineering at SMK Negeri 7 Surabaya provides basic lessons about electric lighting. In practicum learning activities carried out, it is still not optimal and effective. This can be seen from the lack of understanding of students to realize the theory given in the practicum carried out. Based on the results of observations made at SMK Negeri 7 Surabaya, especially in the Electrical Installation Engineering Department, it was found that during the learning process students were still not actively involved, did not understand the theory of the practicum that had been done. In addition, the learning model that is often applied is the Project Based Learning learning model. However, in fact the ability of students in theory is still not optimal, especially practical abilities. Therefore, the learning model used does not only focus on practice but also emphasizes theory to improve student competency. This study aims to determine the effect of critical thinking skills and PjBL learning models on improving learning outcomes of electric lighting installation for class IX TITL students of SMK Negeri 7 Surabaya. In this study using the type of Pre-Experimental research, aims to determine the increase in student learning outcomes on critical thinking skills and the application of Project Based Learning. The study used the Non-Equivalent Control Group Pretest-Posttest form, with purposive random sampling. This research was conducted at SMK Negeri 7 Surabaya, Department of Electrical Installation Engineering, with a population of students at SMK Negeri 7 Surabaya, Class XI TITL Electrical Installation Engineering Expertise Program and two classes were selected at random. The data collection technique used is the test method, student responses, and observation. The data analysis technique uses quantitative analysis. The results of the first hypothesis were obtained, namely a significance value of <0.05, with a significance 0.001. In the second hypothesis, the significance value is <0.05, with a significance 0.033. In the third hypothesis, the significance value is >0.05, with a significance 0.141. So it can be concluded that there is an influence of the Project Based Learning learning model assisted by the E-Job Sheet and the Project Based Learning learning model without the E-Jobsheet on student learning outcomes in the subject of electric lighting installation, there is an influence on learning outcomes between students who have high critical thinking skills and low critical thinking skills in electric lighting installation subjects, and there is nothing interaction between project based learning models assisted by E-Jobsheets and project based learning without E-Jobsheets on learning outcomes in terms of students' critical thinking skills in class electric lighting installation subjects XI TITL SMK Negeri 7 Surabaya.